A combined DFT and experimental study of proline/β-cyclodextrin inclusion complex - Zaboub,A.; Madi,F.; Merdes,R.; Mohamedi,M.; Nouar,L. (My University, 2016)
The binding of the L-proline (Pro) amino acid with β-cyclodextrin (β-CD) was investigated theoretically by B3LYP/3-21G+ method and experimentally by UV–visible and FTIR techniques. Two modes of complexation were considered for studying such complex; in A complex the pyrrolidine ring of the guest was directed toward secondary hydroxyls of β-CD, while in B complex the pyrrolidine was directed toward primary one. Energetic analysis indicates that the formed complexes are stable and both host and guest were deformed after complexation. Electronic properties given by TD-DFT calculation and NBO analysis clearly demonstrate that a charge transfer was occurring between Pro and β-CD molecules.